Crematorium. Irkutsk history - Demkov, Sergey (project baikal, 2025)
The article is devoted to the design of a crematorium complex in Irkutsk. It describes the exterior of the crematorium and functional division of its territory, as well as its characteristics in comparison with the capital and foreign analogues.